Pertumbuhan Tunas Lidah Buaya (Aloe barbadensis Mill.) Dengan Penambahan Naftalene Acetic Acid (NAA) dan Benzyl Amino Purine (BAP) Secara In Vitro - Riza Linda, Nova Anggela, Mukarlina (Jurnal Protobiont, 2017)
Aloe vera (Aloe barbadensis Miller) is one of plants consumed by many poeple. This plant can be regenerated using in vitro culture to get identical plants as their mother plants with many seeds in short time by adding NAA and BAP. This research work aimed to investigate the effect of NAA and BAP on growth of Aloe vera’s shoots. This research was conducted from December 2016 to January 2017 at tissue culture laboratory of Aloe Vera Centre Pontianak. The treatments were arranged in a completely randomized design with two factor. The first factor, NAA (0 M , 10-6M , 5×10-6 M , 10-7 M) and the second factor BAP (0 M , 10-6M , 5×10-6 M , 10-7 M) were aplicated. The research finding indicated that the single NAA and BAP treatmnet and their interaction did not give significant effect, however, the treatments descriptively enhanced growth of shoots, leaves, and roots contens. The treatment for of 0 NAA + 10 7 BAP and 10 -7 NAA + 10-7 BAP enhanced 1 shoot, the treatment of 5 × 10-6 NAA + 5 × 10-6 BAP generated 2,33 leaves, and concentrtion 5 × 10-6 NAA + 10-6 BAP generated 2,66 roots.